Lysine acetylation plays a role in the allograft-induced stress response of the pearl oyster (Pinctada fucata martensii). Issue 130 (November 2022) - Lu, Jinzhao; Fang, Xiaochen; Liang, Haiying; Guo, Zhijie; Zou, Hexin
Abstract: Implanting a spherical nucleus into a recipient oyster is a critical step in artificial pearl production using the pearl oyster Pinctada fucata martensii . However, little is known about the role of post-translational modifications (PTMs) in the response of the pearl oyster to this operation. Lysine acetylation, a highly conserved PTM, may be an essential adaptive strategy to manage multiple biotic or abiotic stresses. We conducted the first lysine acetylome analysis of the P. f. martensii gill 12 h after nucleus implantation, using tandem mass tags (TMT) labeling and K ac affinity enrichment. We identified 2443 acetylated sites in 1301 proteins, and 1511 sites on 895 proteins were quantitatively informative. We found 25 conserved motifs from all of the identified lysine sites, particularly motifs K ac H, K ac S, and K ac Y were strikingly conserved, of which K ac Y, K ac H, Y K ac, K ac K, K ac *K, K ac R, and K ac F which have been observed in other species and are therefore highly conserved. We identified 58 sites that were significantly differently acetylated in P. f. martensii in response to allograft (|fold change|>1.2, P-value ≤ 0.05); 38 newly acetylated and 20 deacetylated. According to GO functional analysis, subcellar location, and KOG classIfication, these proteins were divided into four categories: cytoskeleton, response to stimulus, metabolism, and other. The differentially acetylated proteins (DAPs) enriched pathways include aminoacyl-tRNA biosynthesis, salmonella infection, and longevity regulating pathway-worm-Caenorhabditis elegans (nematode). Parallel reaction-monitoring (PRM) validation of the differential acetylation of 10 randomly selected differentially acetylated sites from the acetylome analysis. These results indicated that our acetylome analysis results were sufficiently reliable and reproducible. These results provide an essential resource for in-depth exploration of the stress responses and adaptation mechanisms associated with lysine acetylation in marine invertebrates and P. f. martensii . Highlights: Allograft-induced lysine acetylome was first studied in Pinctada fucata martensii. The DAPs were associated with cytoskeleton, response to stimulus, metabolism, and other. Three KEGG pathways including aminoacyl-trNA biosynthesis were significantly enriched in DAPs.